Hegel’s Philosophy of Right, with Marx’s Commentary - Kainz, H.P. author. aut Link
VI, 87 p.
Keywords: GEORG WILHELM FRIEDRICH HEGEL (1770-1831) THE PLACE OF HEGEL IN THE HIS TOR Y OF PHILOSOPHY In order to gain a proper perspective of Hegel's place in the history of philo sophy, it might be useful to focus on one key concept which has evolved significantly in meaning, from the time of Aristotle to Hegel. I am speaking of the philosophical concept of the "category. " In Aristotle's system, there were ten categories (or "predicaments") of reality or being. These included substantiality, time, place, quantity, quality, and other aspects of knowable beings. The most notable thing about these categories is that they all have to do with what we would call "objective" realities. That is, none of them purport to describe subjective or mental states or conditions. In modern philosophy (i. e. , philosophy since the time of Descartes), there was a swing of the pendulum in the opposite direction, from objectivity to subjectivity - culminating in the twelve new "categories" of Kant. All of Kant's categories were subjective ways oflooking at reality: We can organize objective phenomena into universal unities; therefore the first Kantian cate gory is "unity. " We can separate objective phenomena into particular divi sions; therefore the second category is "plurality. " And so forth. With Hegel, the modern trend to subjectivism is arrested, and we have, not surprisingly, a new type of "category" - the category of the unity of thought and being, of self and other, of subject and object.